Marsupialization of a Cyst of the Nictitating Membrane in a Dog - Magdanelo Leandro, Rafael; Barbosa, Andréa; de Paula Freitas, Fernando; Safatle Telles, Iris (Acta Scientiae Veterinariae, 2025)
Background: Prolapse of the nictitating membrane gland (PNMG) is the most common primary disorder of the third eyelid in dogs. The development of lacrimal cysts has been reported as a possible complication following surgical repositioning of the gland using the “pocket” technique, and such cysts may compromise lacrimal function and patient comfort. Although various surgical approaches have been described, nictitating membrane marsupialization has proven to be effective in managing these lesions. The objective of this case report was to describe the application of the marsupialization technique as a treatment for a nictitating membrane lacrimal cyst in a dog. Case: A 6-month-old male Beagle presented with a history of a pink mass associated with the left nictitating membrane, causing mild ocular discomfort. The patient had a previous history of bilateral surgical correction of PNMG using the Pocket technique, performed 2 months earlier by a referral veterinarian. After the procedure, the patient showed progressive signs of ocular discomfort, such as epiphora, conjunctival hyperemia, blepharospasm, and mucopurulent discharge. The patient had been treated with Tobradex, applied 4 times daily to the left eye (OS), without improvement. During a complete ophthalmologic examination, a mass was observed upon eversion of the nictitating membrane, and it was fluctuant in consistency. No corneal, anterior chamber, or lens abnormalities were observed. Schirmer Tear Test 1 (STT 1) results were: right eye (OD), 11 mm/min; left eye (OS), 18 mm/min. The Fluorescein test was negative. Tonovet was performed, showing intraocular pressures of 15 mm Hg in the OD and 14 mm Hg in the OS. No changes were noted on indirect fundoscopy. Cytological examination of the mass was performed via fine needle aspiration under topical anesthesia Anestalcon (5 mg/mL), revealing absence of cellularity; the bacterial culture was negative, classifying the content as non-septic fluid. The diagnosis was a nictitating membrane lacrimal cyst (NMLC), and marsupialization was elected as the treatment. Postoperative recommendations included the use of an Elizabethan collar for 15 days. Prescribed medications included: amoxicillin with potassium clavulanate [22 mg/kg every 12 h for 10 days], prednisolone (0.5 mg/kg every 24 h for 7 days), topical ophthalmic treatment with Maxidex (1 mg/mL) 4 times daily for 7 days, Tobrex (0.3%) 4 times daily for 7 days, and the ophthalmic lubricant Hyabak (0.15%) 3 times daily for 10 days. Discussion: Postoperative follow-up consisted of regular evaluations over a 2-year period, during which no aesthetic, clinical, or tear production alterations were observed. The marsupialization technique proved to be a safe and effective approach for treating nictitating membrane cysts secondary to PNMG correction via the conjunctival Pocket technique. This approach allowed for gland preservation, prevented recurrence of cystic cavities, and provided a satisfactory cosmetic outcome. This case highlights the importance of early diagnosis and appropriate surgical planning in managing complications following PNMG correction. Marsupialization not only resolves the cystic lesion but also maintains the tear production function of the gland, which is essential for ocular surface health. Further studies with larger patient populations could help validate this technique as a standard approach for similar cases. Keywords: lacrimal cyst, marsupialization, nictitating membrane, dog.